Од малог грађанина до принца карневала: Однос карневализације и обликовања идентитета у Чаробном брегу Томаса Мана (Philological Studies, 2019)
The goal of this study is to use a genre-poetical and literary-historical base to analyze the possibility of establishing a specific sub-genre core in The Magic Mountain, which is created through a multicenturies tradition of menippean satire and the carnivalization of literature on the one hand, and modernism on the other. From the thematic-motive and semantic context in this novel, one can delineate the crucial question of identity (hero, society, the work itself), so that this new genre sub-group of carnivalized modernistic literature, represented by the novel The Magic Mountain, can be characterized as carnival-identity literature, or rather, it will be shown in this work that carnivalization in modern literature is closely linked with the question of identity formation.
Keywords: carnival, carnivalization, irony, grotesque, parody, humor, modernism, dialoguezation, metamorphosa